Cause analysis and countermeasure for capsizing accident of a dredge fishing boat - Sung-Wook Ohn; Ho Namgung (Journal of International Maritime Safety, Environmental Affairs, and Shipping)
According to maritime accident statistics, capsizing accidents in Korean waters have been increasing annually over past five years, thus demanding urgent countermeasures. In this study, the stability of Yeonggwang, a small dredge fishing boat subjected to a capsizing accident, is numerically simulated at the time of departure from the fishing port and during trawling and hauling. The study analyze stability by calculating and simulating values based on target vessel’s fishing methods and gear characteristics, from departure to capsizing. Based on analysis, countermeasures for capsizing accidents were proposed. The inclination moment is caused by cargo loaded on the bag net during hauling. In this instance, the list and trim angles are determined to be 15.4° and –6.5°, respectively. Consequently, during hauling step, the inclination exceeded the 15 degree threshold for initial stability. The resulting inclination moment caused immediate seawater ingress and a rapid increase in list inclination, leading to capsizing. This study proposes countermeasures, such as uniform cargo arrangement in the field, output control, fishing gear arrangement, and application of alert systems as safety operation equipment to prevent fishing boat capsizing accidents. The proposed countermeasures highlight the need for safety education and legal/policy supplementation for advanced responses in the field.